Gestión del talento humano para ejecución de contratos de obra civil en empresas constructoras - Fuentes Armijos, Maylon Isaac (2023)
This research work analyzes the processes of human talent management in construction companies that execute civil works contracts, among the processes to be investigated are the conditions of the collaborators' work environment, work environment, training programs or training aimed at the workers and technicians of the works, which contributes to the performance of the activities on site. In chapter I, the general framework of the investigation was presented, the problem to be investigated was raised: in addition, the formulation, systematization, delimitation of the problem, objectives of this investigation, idea to defend and the variables.......